Protection against 1-methyl-4-phenyl pyridinium-induced neurotoxicity in human neuroblastoma SH-SY5Y cells by Soyasaponin I by the activation of the phosphoinositide 3-kinase/AKT/GSK3β pathway. Issue 10 (6th July 2016) - Guo, Zheng; Cao, Wei; Zhao, Shifeng; Han, Zengtai; Han, Boxiang
Abstract : Parkinson's disease (PD) can be ascribed to the progressive and selective loss of dopaminergic neurons in the substantia nigra pars compacta, and thus molecules with neuroprotective ability may have therapeutic value against PD. In the current study, the neuroprotective effects and underlying mechanisms of Soyasaponin I (Soya-I), a naturally occurring triterpene extracted from a widely used ingredient in many foods, such as Glycine max (soybean), were evaluated in a widely used cellular PD model in which neurotoxicity was induced by 1-methyl-4-phenyl pyridinium (MPP + ) in cultured SH-SY5Y cells. We found that Soya-I at 10–40 μM considerably protected against MPP + -induced neurotoxicity as evidenced by an increase in cell viability, a decrease in lactate dehydrogenase release, and a reduction in apoptotic nuclei. Moreover, Soya-I effectively inhibited the elevated intracellular accumulation of reactive oxygen species as well as the Bax/Bcl-2 ratio caused by MPP + . Most importantly, Soya-I markedly reversed the inhibition of protein expression of phosphorylated AKT and phosphorylated GSK3β caused by MPP + . LY294002, the specific inhibitor of phosphoinositide 3-kinase, significantly abrogated the upregulated phosphorylated AKT and phosphorylated GSK3β offered by Soya-I, suggesting that the neuroprotection of Soya-I was mainly dependent on the activation of the phosphoinositide 3-kinase/AKT/GSK3β signaling pathway. The results taken together indicate that Soya-I may be a potential candidate for further preclinical study aimed at the prevention and treatment of PD.